2020
DOI: 10.3390/geosciences11010004
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Landform and Landslide Susceptibility Using Remote Sensing, GIS and Field Observation in the Southern Cross Road, Malang Regency, East Java, Indonesia

Abstract: There has been an increasing trend of land area being brought under human’s use over time. This situation has led the community to carry out land-use development activities in landslide hazard-prone areas. The use of land can have a positive impact by increasing economic conditions, but it can have negative impacts on the environment. Therefore, this study aimed to identify the landslide hazard, focusing on the development of a landform map to reduce the risk of landslide disaster in JLS, Malang Regency. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 52 publications
0
19
0
2
Order By: Relevance
“…It was found that Malang Regency had a PGA value of 0.358 gal (Kumala, 2016). Based on remote sensing, GIS, and field observations, this is different from this research because the subject of disaster mitigation is different, namely for landslide disaster mitigation (Bachri et al, 2021). The results of this study were not detailed.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…It was found that Malang Regency had a PGA value of 0.358 gal (Kumala, 2016). Based on remote sensing, GIS, and field observations, this is different from this research because the subject of disaster mitigation is different, namely for landslide disaster mitigation (Bachri et al, 2021). The results of this study were not detailed.…”
Section: Introductionmentioning
confidence: 76%
“…This research was conducted in Malang Regency with coordinates 7.22° -9.52° S and 112.12° -112.60° E (Figure 2). The physiographical conditions of Malang (Figure 2) are highly variable and dominated by undulating and hilly soil that is prone to landslides (Bachri et al, 2021). Then, Malang was divided into several parts with a grid size of 0.025º x 0.025º to make it easier to read the results of the calculation of the PGA value and the intensity of the earthquake in each regency.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the rainfall intensity at the average rainfall is ranging from 0 mm to 602 mm (BPS of Malang Regency, 2020). Based on the landform configuration, the study area is dominated by hilly and strong erosion processes (Bachri et al, 2021). Detail of landform identification within the study area can be seen in below Table 2.…”
Section: Toward a Physical Environment Of The Study Areamentioning
confidence: 99%